2018
DOI: 10.3390/su10124376
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Synergies and Trade-Offs between Ecosystem Services to Reorient Land Use Planning in Metropolitan Bilbao (Northern Spain)

Abstract: In the last decades, some European cities have undergone important changes in search of a more sustainable development. This is the case for the city of Bilbao (Bizkaia, Basque Country), where a Greenbelt has been maintained surrounding the urban areas allowing the periurban areas to deliver ecosystem services (ES) to society. However, the role of the different ecosystems in the provision of ES is not the same, which can lead to conflicts among them. The aim of this study is to analyze the synergies and trade-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 90 publications
1
10
0
1
Order By: Relevance
“…The EM approach hence integrates measures of the relative supply of multiple ecosystem functions and services to evaluate multiple restoration targets based on a high number of individual indicators (Strobl et al, 2019). The multifunctional nature of ecosystems and the proposed multifunctionality approach cause the need to consider synergies and trade-offs between ES and functions (Raudsepp-Hearne et al, 2010;Gamfeldt et al, 2013;Peña et al, 2018). Berry et al (2020), for example, discussed synergistic relationships between carbon storage and biodiversity, whereby the provision on one allowed for greater levels of the other.…”
Section: Introductionmentioning
confidence: 99%
“…The EM approach hence integrates measures of the relative supply of multiple ecosystem functions and services to evaluate multiple restoration targets based on a high number of individual indicators (Strobl et al, 2019). The multifunctional nature of ecosystems and the proposed multifunctionality approach cause the need to consider synergies and trade-offs between ES and functions (Raudsepp-Hearne et al, 2010;Gamfeldt et al, 2013;Peña et al, 2018). Berry et al (2020), for example, discussed synergistic relationships between carbon storage and biodiversity, whereby the provision on one allowed for greater levels of the other.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, first of all, within the CoP, the priority regulating ES were identified (habitat maintenance, air purification, carbon storage, water flow regulation, and pollination) [28]. Subsequently, their spatial distributions were mapped (very high, high, medium, low and very low) in accordance with the methodology outlined in [29,30], and the maps of these ES were overlaid. Those areas that had high or very high values for all ES were identified as principal components, and those with high or very high values for four of them were identified as secondary components [31].…”
Section: Proposal For a Regional Green Infrastructure Using The Esamentioning
confidence: 99%
“…ES provision was positively related to the amount of vegetation and negatively related to its degree of fragmentation. Peña et al (2018) found that provisioning services had trade-offs with regulating services and cultural services in Bilbao (in an area that covers 413 km 2 ). Synergies were found between cultural services and between regulating services.…”
Section: Introductionmentioning
confidence: 99%